(3TQM GdebOeI hGdOjHGLI ddeaGJjMs - (3GdHgHgGfj, GdcQeGfTGgj, GHf GdhMjO, eMeO Ydj, J (B1216(3g`s
(3ChdgG (B:s
(3CMeOg Ydi fhGdg eUdjG Ydi(B...(3hBdg hHYO ajbhd GdYGde(B...(3bO gOGfj bGFO GdJhajb Edi efgd GdJMbjb hGdJObjb(B...s
(3BNQgG (B:s
(3eHJhQ GdBNQ, hjfJgj CKfGA JQGLe dHYV YdeGA GdYGeI hBNQg ef JQLeI (B((3YGeQ Hf TQGMjd(B) (3Hbhdg(B: (3hcGf VFjdG fMjaG abjd dg aj Pdc abGd(B: (3RhMeJ aj GdQMe hcGf bO hdO hCN BNQ aj HWf hbGe aj GdHWf SfJjf PcQg aj cJGH GdeYGQas
(3JHUQI GdYfhGf (B:s
(3hPcQ aj GdPQjYI Cf GSeg (B((3eaJGM GdeLGeY(B)s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdPQjYI(B:(3L(B14(3,U(B49(3,JMJ Qbe (B1811s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
Keywords: (3abg GdePGgH GdCNQis